Implementation of Government Regulation No.46 Year of 2013 and No.23 Year of 2018 For Small and Medium Enterprises of Bandung City (Case Study of Small and Medium Enterprises in Bandung City) - Eka Dyah Setyaningsih; Ratiyah* Ratiyah; Hartanti Hartanti; Vera Agustina Yanti; Sumanto Sumanto (LPPM Universitas BSI, 2020)
This study aims to analyze the growth of turnover from the three types of businesses in the fields of convection, food processing, and study, by comparing the application of the UMKM tax calculation based on PP No 46 of 2013 and PP No 23 of 2018. The sampling technique uses unproportioned stratified random sampling and is carried out in December 2018 until June 2019. Data analysis in this study uses descriptive qualitative analysis by socializing the UMKM tax calculation with the most recent simple calculation following government regulations, which is 0.5% of turnover which was previously 1% of turnover. The results showed in Bandung Regency, namely the type of convection business with the highest turnover of Rp. 3,000,000,000 and the lowest is Rp. 960,000,000; type of food processing business, the highest turnover is Rp. 600,000,000, and the lowest is Rp. 132,000. 000, -; and by the type of handicraft business with the highest turnover of Rp. 600,000,000 and the lowest Rp. 96,000,000 By using PP 46 of 2013 with a turnover rate of 1% per year, updated to PP 23 of 2018 at a rate of 0.5% per year, through this policy it has been generated that UMKM entrepreneurs will be lighter with payment of a 0.5% tax rate to be able to stimulate UMKM entrepreneurs to continue working and building new innovations in their industrial business. Related to this pandemic period for SMEs in Bandung regency still lacking understanding of UMKM tax incentives, from the Directorate General of Central and Regional Taxes to make publications and socialization efforts so that people follow this opportunity